Image-guided high-dose-rate brachytherapy of malignancies in various inner organs – technique, indications, and perspectives - Bretschneider, Tina; Ricke, Jens; Gebauer, Bernhard; Streitparth, Florian (Journal of Contemporary Brachytherapy, 2016)
In the last few years, minimally invasive tumor ablation performed by interventional radiologists has gained increasing relevance in oncologic patient care. Limitations of thermal ablation techniques such as radiofrequency ablation (RFA), microwave ablation (MWA), and laser-induced thermotherapy (LITT), including large tumor size, cooling effects of adjacent vessels, and tumor location near thermosensitive structures, have led to the development of image-guided high-dose-rate (HDR) brachytherapy, especially for the treatment of liver malignancies. This article reviews technical properties of image-guided brachytherapy, indications and its current clinical role in multimodal cancer treatment. Furthermore, perspectives of this novel therapy option will be discussed.